2018
DOI: 10.1111/dom.13497
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid‐1 receptor regulates mitochondrial dynamics and function in renal proximal tubular cells

Abstract: CB R plays a key role in inducing mitochondrial fragmentation in RPTCs, leading to a decline in the organelle's function and contributing to the renal tubular injury associated with lipotoxicity and other metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 74 publications
2
27
0
1
Order By: Relevance
“…Nevertheless, we could not completely rule out the obligatory role of CB 1 receptors in modulating renal oxidative stress as well, because knocking it out in RPTCs protected the cells from O:P-induced lipid oxidation and oxidative stress. These results support our previous findings in mice lacking CB 1 receptors specifically in RPTCs, which are completely protected from the deleterious effects of HFD feeding and fatty acid flux-induced renal dysfunction, inflammation, mitochondrial damage, oxidative stress, and fibrosis (Drori et al, 2019;Udi et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, we could not completely rule out the obligatory role of CB 1 receptors in modulating renal oxidative stress as well, because knocking it out in RPTCs protected the cells from O:P-induced lipid oxidation and oxidative stress. These results support our previous findings in mice lacking CB 1 receptors specifically in RPTCs, which are completely protected from the deleterious effects of HFD feeding and fatty acid flux-induced renal dysfunction, inflammation, mitochondrial damage, oxidative stress, and fibrosis (Drori et al, 2019;Udi et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This comes in addition to previous reports of non-receptor specific effect of cannabinoids on mitochondria [89,90]. Interestingly, it has been shown that the CB1-mediated effect on mitochondrial dynamics is not restricted to cells of the nervous system [91]. In this study, it is shown that CB1 stimulation by the endocannabinoid, n-arachidonoylethanolamine (AEA), in renal proximal tubular cells leads to dynamin-related protein 1 (DRP1) activation, with its subsequent translocation to the mitochondria that results in mitochondrial fission.…”
Section: Cannabinoids Mitochondria and The Nervous Systemsupporting
confidence: 71%
“…eCBs were extracted, purified, and quantified in liver homogenates, as described previously ( Drori et al, 2019 ; Udi et al, 2017 ). LC-MS/MS was analyzed on an AB Sciex (Framingham, MA, USA) Triple Quad 5500 mass spectrometer coupled with a Shimadzu (Kyoto, Japan) UHPLC System.…”
Section: Methodsmentioning
confidence: 99%